2013
DOI: 10.1371/journal.pone.0067990
|View full text |Cite
|
Sign up to set email alerts
|

β5 Integrin Up-Regulation in Brain-Derived Neurotrophic Factor Promotes Cell Motility in Human Chondrosarcoma

Abstract: Chondrosarcoma is a primary malignant bone cancer, with a potent capacity to invade locally and cause distant metastasis; it has a poor prognosis and shows a predilection for metastasis to the lungs. Brain derived neurotrophic factor (BDNF) is a small-molecule protein from the neurotrophin family of growth factors that is associated with the disease status and outcomes of cancers. However, the effect of BDNF on migration activity in human chondrosarcoma cells is mostly unknown. Here, we found that human chondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…Exploration of signalling pathways in our study showed that PI3/Akt pathway seemed to be more activated than ERK1/2 pathway in GCA patients compared to controls. Though PI3/Akt signalling pathway can be activated by TNF-α in human smooth muscle cells [ 32 ] or IL-1β in rat brain astrocytes [ 33 ], our results are consistent with BDNF-induced migration in human chondrosarcoma [ 34 ] through a transducing signal involving TrkB.…”
Section: Discussionsupporting
confidence: 84%
“…Exploration of signalling pathways in our study showed that PI3/Akt pathway seemed to be more activated than ERK1/2 pathway in GCA patients compared to controls. Though PI3/Akt signalling pathway can be activated by TNF-α in human smooth muscle cells [ 32 ] or IL-1β in rat brain astrocytes [ 33 ], our results are consistent with BDNF-induced migration in human chondrosarcoma [ 34 ] through a transducing signal involving TrkB.…”
Section: Discussionsupporting
confidence: 84%
“…Our previous studies have shown that BDNF is associated with chondrosarcoma metastasis and angiogenesis. 16 , 17 , 18 VEGF-C has been reported to mediate tumor lymphangiogenesis in many human cancers. 19 , 20 However, the effect of BDNF on VEGF-C expression and lymphangiogenesis in chondrosarcoma has not been well explored.…”
Section: Resultsmentioning
confidence: 99%
“… 14 , 15 Our previous research has proposed that BDNF promotes chondrosarcoma metastasis through the upregulation of integrin β 5 and matrix metalloproteinase-1 expression. 16 , 17 Moreover, we have described how BDNF induces VEGF-A expression and angiogenesis in human chondrosarcoma cells. 18 VEGF-C is known to mediate tumor lymphangiogenesis in many human cancers.…”
mentioning
confidence: 99%
“…14,21 In BDNF-enhanced migration of chondrosarcoma, integrin β5 expression was up-regulated through TrkB/AKT signalling cascade, while in BDNF-mediated migration of microvascular endothelial cells, the up-expression of integrin β3 was made via TrkB/ERK1/2 pathway. 14,21 Besides integrin β3 and integrin β5, our study found BDNF also could regulate integrin β1 expression for the first time and both AKT and EKR1/2 acted as two parallel downstream kinases in BDNF/TrkB signalling. As integrins often appeared as α/β heterodimeric receptors, further studies should be made to understand which α subunit was involved in BDNF-integrin β1 controlled osteoblasts migration.…”
Section: Discussionmentioning
confidence: 99%
“…Cooperating with kinds of growth factors, integrins transduce signals from the environment into cells and often mediate cell adhesion and migration. 14,[19][20][21] Xiong suggested TGFβ1 induced endometrial cancer cell adhesion and migration by up-regulating integrin αvβ3 while Furmento indicated granulocyte colony-stimulating factor (G-CSF) up-regulated integrin β1 and increased migration of human trophoblast Swan 71 cells. 19,20 For BDNF signalling, integrin β3 and β5 has already been proved to be up-regulated and participate in manipulating endothelial and chondrosarcoma cells migration, respectively.…”
mentioning
confidence: 99%